2010
DOI: 10.1007/s10792-010-9406-8
|View full text |Cite
|
Sign up to set email alerts
|

Bietti crystalline dystrophy and choroidal neovascularisation

Abstract: Bietti crystalline dystrophy is a rare autosomal recessive condition characterised by the presence of crystals in the retina and is followed by retinal and choroidal degeneration. We present a novel finding of juxtafoveal choroidal neovascularisation in Bietti crystalline dystrophy and demonstrate a spectral domain optical coherence tomography image of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Bietti crystalline dystrophy can be associated with other sight-threatening complications, including cystoid macular edema, choroidal neovascularization, and macular hole. [13][14][15][16][17][18][19][20][21] Fluorescein and Indocyanine Green Angiography Findings Fluorescein angiography changes correlate well with clinical findings and progression in BCD. 12,22,23 In the early stage of BCD, hyperfluorescence due to window defects appears in areas of RPE atrophy with intact choriocapillaris.…”
Section: Fundus and Anterior Segment Features Of Bcdmentioning
confidence: 74%
See 1 more Smart Citation
“…Bietti crystalline dystrophy can be associated with other sight-threatening complications, including cystoid macular edema, choroidal neovascularization, and macular hole. [13][14][15][16][17][18][19][20][21] Fluorescein and Indocyanine Green Angiography Findings Fluorescein angiography changes correlate well with clinical findings and progression in BCD. 12,22,23 In the early stage of BCD, hyperfluorescence due to window defects appears in areas of RPE atrophy with intact choriocapillaris.…”
Section: Fundus and Anterior Segment Features Of Bcdmentioning
confidence: 74%
“…49,55 Interestingly, clinical symptoms of BCD remain only in the eyes. The link between altered 32 Yin et al, 36 Meng et al, 59 Manzouri et al, 64 Shan et al 60 15 3 c.332T>C p.I111T Missense Li et al, 55 Astuti et al, 63 Rossi et al, 61 García-García et al, 65 Haddad et al, 66 Rossi et al 67 10 Lin et al, 11 Li et al, 17 Gocho et al, 27 Halford et al, 32 Yin et al, 36 Li et al, 55 Xiao et al, 57 Meng et al, 59 Astuti et al, 63 Nakamura et al, 68 Lee et al, 69 Chung et al, 70 Gekka et al, 71 Jin et al, 72 Liu et al, 73 Shan et al, 60 Tian et al, 62 Wada et al, 74 10 Li et al, 17 Li et al, 55 Xiao et al, 57 Meng et al, 59 36 Meng et al, 59 Mamatha et al 77 43 9 c.1091-2A>G Exon9del Splice site Li et al, 17 Yin et al, 36 Li et al, 55 Xiao et al, 57 Meng et al, 59 Shan et a...…”
Section: Role Of Cyp4v2 In Fatty Acid Metabolismmentioning
confidence: 99%
“…6-11 While some reports have shown that CNV can regress without intervention, 5, 6 other studies have reported the success of anti-VEGF agents in CNV associated with BCD. 7, 9, 10 In our patient, in the presence of active CNV and metamorphopsia, anti-VEGF treatment was instituted, resulting in improved visual acuity and decreased visual distortion, supporting the role of the VEGF pathway in the pathophysiology of CNV in BCD and of a role of anti-VEGF therapy in the treatment of CNV in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, CNV infrequently occurs in patients affected by hereditary retinal dystrophies [21]. To date, there are only four reports of BCD associated with the phenotype of CNV [14], [22], [23], [24],whereas none of them identified causative mutations in CYP4V2 or other genes associated with CNV, such as tissue inhibitor of metalloproteinase 3 ( TIMP3 ) [14], [25]. In addition, the phenotype of BCD associated with a macular hole was only briefly described in two studies without genetic analysis [26], [27].…”
Section: Introductionmentioning
confidence: 99%